Negative nonlinear absorption in Er3+-doped fluoroindate glass - Lozano, W.; de Araujo, C. B.; Acioli, L. H.; Messaddeq, Younes [UNESP] (American Institute of Physics (AIP), 1998)
We report the observation of negative nonlinear absorption in fluoroindate glasses doped with erbium ions. The pumping wavelength is 800 nm which is doubly resonant with Er3+ ions transitions. A large nonlinear intensity dependence of the optical transmittance and strong upconverted fluorescence are obtained. The dependence of the upconverted fluorescence intensity with the laser power is described by a system of coupled-rate equations for the energy levels' populations. (C) 1998 American Institute of Physics. [S0021-8979(98)07816-5].